Safety and immunogenicity of one dose of MenACWY-CRM, an investigational quadrivalent meningococcal glycoconjugate vaccine, when administered to adolescents concomitantly or sequentially with Tdap and HPV vaccines - Arguedas, A.; Soley, C.; Loaiza, C.; Rincon, G.; Guevara, S.; Perez, A.; Porras, W.; Alvarado, O.; Aguilar, L.; Abdelnour, A.; Grunwald, U.; Bedell, L.; et al. (Vaccine, 2010)
This Phase III study evaluates an investigational quadrivalent meningococcal CRM197 conjugate vaccine, MenACWY-CRM (Novartis Vaccines), when administered concomitantly or sequentially with two other recommended adolescent vaccines; combined tetanus, reduced diphtheria and acellular pertussis (Tdap), and human papillomavirus (HPV) vaccine. In this single-centre study, 1620 subjects 11–18 years of age, were randomized to three groups (1:1:1) to receive MenACWY-CRM concomitantly or sequentially with Tdap and HPV. Meningococcal serogroup-specific serum bactericidal assay using human complement (hSBA), and antibodies to Tdap antigens and HPV virus-like particles were determined before and 1 month after study vaccinations. Proportions of subjects with hSBA titres ≥1:8 for all four meningococcal serogroups (A, C, W-135, Y) were non-inferior for both concomitant and sequential administration. Immune responses to Tdap and HPV antigens were comparable when these vaccines were given alone or concomitantly with MenACWY-CRM. All vaccines were well tolerated; concomitant or sequential administration did not increase reactogenicity. MenACWY-CRM was well tolerated and immunogenic in subjects 11–18 years of age, with comparable immune responses to the four serogroups when given alone or concomitantly with Tdap or HPV antigens. This is the first demonstration that these currently recommended adolescent vaccines could be administered concomitantly without causing increased reactogenicity.